Theanine-Modified Graphene Oxide Composite Films for Neural Stem Cells Proliferation and Differentiation. (13th July 2020) - Qi, Zhiping; Chen, Xue; Guo, Wenlai; Fu, Chuan; Pan, Su
Abstract : The central nervous system (CNS) injury has been a worldwide clinical problem for regenerative medicine. Nerve tissue engineering is a new strategy for CNS injury. Among kinds of biomaterials, graphene oxide (GO)-based degradable composite materials are considered to be promising in the field of neurogenesis. In this study, GO and L-theanine (TH) were combined by chemical grafting to prepare a new PLGA/GO-TH composite material. X-ray diffraction (XRD), transmission electron microscope (TEM), Fourier-transform infrared spectra (FTIR), contact angle testers, and mechanical testers were performed to obtain characterization of composite materials. The protein adsorption efficiency of the PLGA/GO-TH films was then evaluated. Next, the effect of the composite films on neural stem cell (NSC) survival, proliferation, and differentiation was investigated. Our results indicated that L-theanine was successfully grafted onto GO. PLGA/GO-TH composite film can significantly improve NSC survival, proliferation, and neuronal differentiation. Our results demonstrated that the neurogenesis function of a novel PLGA/GO-TH composite film and its potential as a carrier for the further application in the CNS injury.